1997
DOI: 10.1038/sj.ijo.0800419
|View full text |Cite
|
Sign up to set email alerts
|

Leptin concentrations and insulin sensitivity in normoglycemic men

Abstract: OBJECTIVE: Leptin is a hormone regulating weight in the mouse. Leptin regulates food intake and appetite. Leptin concentrations are increased in obese individuals suggesting resistance to its effect. However, there is considerable variability in leptin levels at each level of adiposity suggesting that environmental and genetic factors may regulate leptin concentrations. We examined whether subjects with decreased insulin sensitivity have increased leptin levels. METHODS: We used a radioimmunoassay to measure s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
1
1

Year Published

1998
1998
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 29 publications
7
67
1
1
Order By: Relevance
“…In a population of 87 lean men, Haffner et al showed plasma leptin levels were correlated with insulin levels and insulin sensitivity even after controlling for BMI. 23 We extend these results to children and further show that a single assessment of leptin is a better predictor of insulin resistance syndrome than WHR.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a population of 87 lean men, Haffner et al showed plasma leptin levels were correlated with insulin levels and insulin sensitivity even after controlling for BMI. 23 We extend these results to children and further show that a single assessment of leptin is a better predictor of insulin resistance syndrome than WHR.…”
Section: Discussionmentioning
confidence: 91%
“…Leptin, obesity and insulin resistance syndrome among children N-F Chu et al Others also have found that insulin resistance is associated with elevated plasma leptin levels independent of body fat mass, 19,23,28,52 but these studies have been limited to adult populations. In a population of 87 lean men, Haffner et al showed plasma leptin levels were correlated with insulin levels and insulin sensitivity even after controlling for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged hyperinsulinemia is known to increase circulating leptin levels. 8,9,20 In rodents, both in vivo and in vitro studies have demonstrated that leptin increases peripheral glucose uptake and improves glucose metabolism in skeletal muscles. 10 ± 12 Therefore, according to the results obtained in animal models, we cannot exclude the theory that increased leptin production could be a regulatory component aimed at improving, at least in part, insulin-sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Both fasting insulin and insulin sensitivity (hyperinsulinaemic, euglycaemic clamp) were correlated with leptin independently of BMI in middle-aged Finnish men, but no attempt was made to assess which was more important. 42 In subjects with Type 2 diabetes mellitus, the association between insulin concentration and resistance is not as close, and in two studies making use of this phenomenon, leptin was found to be more closely correlated with insulin concentration than with insulin resistance. These inconsistent results indicate the need to standardize the approach to investigations into leptin, insulin and obesity.…”
Section: Leptin and Insulin Sensitivity Pz Zimmet Et Almentioning
confidence: 99%